(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The state Uttarakhand is rich with floral and faunal diversity including plants used by local inhabitance to cure health problems. Himalayan region always has been the treasure of herbs from ancient time. Himalayan herbs are highest in quality and potency. There are numbers of side effect are noted using allopathic medicines which leads towards reuse of medicinal plants available locally. Keeping this in view an attempt has been made to enumerate the common medicinal plants used in traditional therapeutic system of Uttarakhand, India. Results reveal that 29 plant species are used for primary healthcare. Purnagiri hills located in Champavat district of Uttarakhand is reservoir for a large number of medicinal herbs during the field survey large number of medicinal plants like Adina cordifolia (Roxb.) Hook. (Rubiaceae), Asparagus adscendence Roxb. (Liliaceae), Artemesia nilgirica (Clarke) Pamp. (Asteraceae), Berberis aristata DC. (Berberiridaceae), Colebrookea oppositefolia Sm. (Lamiaceae), Elephantopus scaber L (Asreraceae), Pinus longifolia Roxb. (Pinaceae), Tamarix gallica L. (Tamaraceae), Urtica dioica L. (Urtecaceae) and many more with their use in local health traditions by local habitants were recorded. One of the serious challenges to biodiversity and ecological functioning is climate change. Climate change and global warming are well known issue that has had an impact on the biodiversity. Second thing over exploitation of Himalayan forest leads these valuable herbs in endangered category. Some of the plants recorded are critically endangered and rare. We have to pay attention towards the conservation, cultivation of these herbs.